Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/gerona/gly161
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aging, Calorie Restriction and Dietary Fat on Autophagy Markers and Mitochondrial Ultrastructure and Dynamics in Mouse Skeletal Muscle

Abstract: Loss of skeletal muscle mass and function is a hallmark of aging. This phenomenon has been related to a dysregulation of mitochondrial function and proteostasis. Calorie restriction (CR) has been demonstrated to delay aging and preserve function until late in life, particularly in muscle. Recently, we reported the type of dietary fat plays an important role in determining lifespan extension with 40% CR in male mice. In these conditions, lard fed mice showed an increased longevity compared to mice fed soybean o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
5
34
2
Order By: Relevance
“…CR is a long-term dietary intervention characterized by reduced caloric intake, but malnutrition and deficiency of essential nutrients are prevented [12,13]. The health advantages of CR resulting in lifespan extension are well established in many studies [14,15]. Moreover, accumulating evidence indicates that CR represents an effective strategy to reduce weight, influences adipose tissues plasticity, and modifies endocrinological function of adipose tissue and skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…CR is a long-term dietary intervention characterized by reduced caloric intake, but malnutrition and deficiency of essential nutrients are prevented [12,13]. The health advantages of CR resulting in lifespan extension are well established in many studies [14,15]. Moreover, accumulating evidence indicates that CR represents an effective strategy to reduce weight, influences adipose tissues plasticity, and modifies endocrinological function of adipose tissue and skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they found decreased muscle inflammation, suggesting another beneficial role of CR on muscle biology. The study by Gutierrez-Casado et al also showed a prominent effect of CR on autophagy in the muscle [68]. CR resulted in decreased levels of p62, suggesting a possible increase in autophagy flux.…”
Section: Musclementioning
confidence: 84%
“…Muscle mass loss is considered normal with age; however, calorie restricted diets can slow aging and protect muscle. Therefore, Gutierrez‐Casado et al 64 . assessed CR and age on markers of mitophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Muscle mass loss is considered normal with age; however, calorie restricted diets can slow aging and protect muscle. Therefore, Gutierrez-Casado et al 64 assessed CR and age on markers of mitophagy. Ten-week-old mice were divided into four groups: a control group and three CR groups with different sources of dietary fat (lard, fish oil, or soybean oil) for 6 or 18 months.…”
Section: Fasting or Calorie Restriction And Mitophagymentioning
confidence: 99%